2005
DOI: 10.1128/iai.73.12.8039-8049.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Intestine Selects Nonmotile flhDC Mutants of Escherichia coli MG1655 with Increased Colonizing Ability and Better Utilization of Carbon Sources

Abstract: D-Gluconate which is primarily catabolized via the Entner-Doudoroff (ED) pathway, has been implicated as being important for colonization of the streptomycin-treated mouse large intestine by Escherichia coli MG1655, a human commensal strain. In the present study, we report that an MG1655 ⌬edd mutant defective in the ED pathway grows poorly not only on gluconate as a sole carbon source but on a number of other sugars previously implicated as being important for colonization, including L-fucose, D-gluconate, D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(148 citation statements)
references
References 47 publications
(52 reference statements)
13
133
2
Order By: Relevance
“…It was previously shown that a MG1655-derived strain with an flhD mutation that causes the strain to become nonmotile has a significant growth advantage in glycerol M9 minimal medium relative to the parent strain (20). Loss of motility in MG1655 adapted to growth in GMM has previously been observed (21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that a MG1655-derived strain with an flhD mutation that causes the strain to become nonmotile has a significant growth advantage in glycerol M9 minimal medium relative to the parent strain (20). Loss of motility in MG1655 adapted to growth in GMM has previously been observed (21).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 2, representing strongly downregulated genes, was enriched for motility, chemotaxis, cell adhesion (fimbria and curli), and acid resistance genes. Down-regulation of these genes should provide a selective advantage in the growth environment, because their functions are costly in terms of energy but confer little or no benefit (20).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, selective pressures in the intestinal tract tend to counterselect the motility of E. coli. Hence, it was shown that mutations in the flhDC genes and in the two-component system envZ-ompR, drastically affecting the expression of the flagella, give a selective advantage in the intestine of mice (17,36). A parsimonious regulation of the expression of genes involved in motility is required probably because proteins constituting the flagella are immunogenic (4) and costly to produce (14).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this possibility, we used a strategy designed to provide the microbiota with a steady, high level of a rapidly metabolized carbon source. We previously showed that gluconate, which supports the growth of E. coli but is not absorbed by the host, is able to affect the outcome of experiments that depend on competition for gluconate (28). We reasoned that the constant availability of an excess supply of gluconate, provided by adding 2% gluconate to the drinking water of mice throughout the experiment, would rescue the dependence of colonized E. coli on stored glycogen.…”
Section: Vol 76 2008 In Vivo Maltose and Glycogen Metabolism 2535mentioning
confidence: 99%